eGym : make fitness your lifestyle - Sousa, Cristine; Milanovic, Ana; Laker, Maximilian; Gupta, Siddarth; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
It was in 2008 in the campus fitness centers of Columbia University where Philipp Roesch-Schlanderer realized that fitness centers essentially were the same as in the 1960's in terms of general look, feel and equipment available. However, today's trend in personal fitness was not simply about bulking up bodies; the vast majority of modern fitness center members were people trying to improve their physique and fitness as a leisure activity. With this gap between client expectation and service provision and the motivation to revolutionize the fitness industry, the idea for eGym was born. By 2013, eGym as a B2B business had already grown to a considerable size, receiving seed funding to successfully introduce a hardware and software product into the German market. The hardware product was a circuit of high-tech fitness machines that increased workout quality and effectiveness. The software product enabled trainers to deliver individualized customer service.
Originally Published InSousa, C., Milanovic, A., Laker, M., Gupta, S., & Hulsink, W. (2015). eGym: Make fitness Your lifestyle. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; eGym -- Case studies; Strategic planning -- Case studies; New business enterprises -- Case studies